A Factors Associated with Menstrual Disorders in Adolects at SMPN 2 Kota Padangsidimpuan in 2024: Menstrual disorders - harahap, Ghevina diva zahra; Wari Harahap, Yanna; Ritonga, Nefonavratilova (Pena Cendekia Insani, 2024)
Menstrual disorders are abnormalities that occur in the menstrual cycle. Common menstrual disorders can b e divided into five types, namely: Amenorrhea, Dysmenorrhea, Menorrhagia, Oligomenorrhea, Polymenorrhea. Therefore, this study was conducted with the aim of determining the factors related to menstrual disorders in adolescent girls at SMP N 2 Padangsidimpuan City. This type of research i s quantitative with a research design, namely Cross-sectional. The population of this study was 222 and the sample in this study was 69 respondents with a sampling technique using Simple random Sampling. Data were collected through questionnaires and data analysis using the chi Square statistical test with a confidence level of 95% (a = 0.05). The results of the study of anxiety with menstrual disorders showed a p-value (0.663>0.05) and physical activity with menstrual disorders showed a p-value of 0.054>0.05) means that there was no relationship between anxiety and physical activity with menstrual disorders in SMP N 2 Padangsidimpuan City. Research at SMP N 2 Padangsidimpuan showed there is no relationship between anxiety and physical activity with menstrual disorders. However, schools are still advised to provide comprehensive menstrual education, increase awareness o f mental health, educate healthy physical activity, and encourage a healthy lifestyle. Students are advised to monitor their menstrual cycle and consult a doctor if there is a disorder. Further research is needed to determine other factors that may affect menstrual health.